How agri-food value chain employment and compensation evolve with structural transformation - Yi, Jing; Jiang, Shiyun; Tran, Dianna; Gómez, Miguel I.; Canning, Patrick; Bloem, Jeffrey R.; Barrett, Christopher B. (International Food Policy Research Institute, 2024)
The traditional structural transformation narrative emphasizes inter-sectoral labor reallocation out of agriculture, ignoring whether workers exit agri-food value chains or merely migrate within them, from primary agricultural production to downstream food industries. We introduce a method to decompose multiregional input-output table data into industry-and-country-specific annual labor value added estimates by final consumer market segment – domestic food at home, domestic food away from home, or exports – and match with industry-specific employment data to estimate average worker compensation. Using data covering most of the global economy, 1993-2021, we report ten stylized facts that sharpen the traditional narrative about labor reallocation amid structural transformation. As incomes grow, labor exits primary production for downstream agri-food value chain segments that maintain a steady economywide employment share while offering jobs that pay better than farm work. Women disproportionately move from primary production to downstream, consumer-facing retail and food service, while men migrate to better-paying midstream jobs, increasing gender pay inequality within the value chain. Employment shifts are strongly associated with changes in national per capita income, but not with agricultural total factor productivity growth.